MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN ANAK GANGGUAN INTELEKTUAL RINGAN DENGAN MENGGUNAKAN METODE KLOSE - Purwani Budi Astuti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The children of disorder intellectually undemanding should have reading comprehension competence to be able to follow the instructional development optimally. However, many children do not have such competence that they can not understand the reading passages properly. To solve the problem, this research conducted a classroom action research in the fifth grade of SDLB C Dian Kahuripan, Jakarta. Employing Close method in two cycles, the research discovered significant improvement of the students’ reading comprehension competence. The research concludes that Close method with a number of techniques and activities is effective to solve the reading comprehension problems faced by the children of disorder intellectually undemanding